STRATEGI PEMASARAN BUAH TOMAT (STUDI KASUS PADA KELOMPOK TANI SAPTA KERTA BHUANA DI DESA BANGLI, KECAMATAN BATURITI KABUAPTEN TABANAN) - Rikardus Jagang; Ni Gst Ag Gde Eka Martiningsi; Ida Ayu Made Dwi Susanti (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
Marketing is a process that aims to satisfy the needs and desires of consumers, product marketing strategies can be used as steps and solutions taken by tomato farmers to overcome the problems they face. This research aims to: find out internal factors and external factors, formulate alternative strategies, and determine the priority strategies that can be applied in marketing tomatoes to the Sapta Kerta Bhuana Farmers Group in Bangli Kecamtan Baturiti Village of Tabanan Regency. Respondents of 34 people using the census method, with metode analisis data using SWOT and QSPM. Research shows that the internal actors in terms of high strength are good product quality and the highest weakness is the weakening of consumer purchasing power, while external factors in terms of the highest opportunities are having broader marketing and the highest threats. High is the pandemic. Next alternative strategy in research a). optimizing IT development through trainings in digital marketing, b). establish marketing partnerships with private parties, c). maintaining product quality by standardizing the product, d). Maintain price stability at the consumer level. ,e). develop processed products from tomatoes to increase tilapia plus tomatoes, f). make capital loans in increasing production capacity in an effort to reduce production costs and g). increase production capacity through stock management with the intensity of government monitoring through related agencies and h). increase the production capacity of tomatoes in the rainy season by utilizing green houses. Furthermore, the main strategy that can be implemented on the tomato marketing strategy in the Sapta Kerta Bhuana Farmer group in Bangli Kecamatan Baturiti Village of Tabanan Regency is to optimize the development of it through trainings in digital marketing. But it can be suggested to farmers, it is expected to be able to optimize green houses and develop diversification of tomato products so as to increase continuous production capacity and wider Keywords: Marketing Strategy, Tomato, SWOT, QSPM